Problematika Terjemahan Al-Qur’an Studi pada Beberapa Penerbitan Al-Qur'an dan Kasus Kontemporer - Hanafi, Muchlis Muhammad (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
The process of translation is beset with problems. On the one hand, translation demands a faithful transfer of the meaning as contained in the source text into the target language, but on the other hand, the process also requires elegance and beauty in theÃ‚Â choice of words and expressions. These obstacles are magnified when the source text in question is the QurÃ¢â‚¬â„¢an, because it is not a man-made creation or a work of fiction or poetry, but the word of God. This article will explore some of these problems with reference to translations of the QurÃ¢â‚¬â„¢an published by the Ministry of Religious Affairs of the Republic of Indone-sia and three other publishers.